Advances on the growth and properties of N- and B-doped carbon nanotubes - Terrones, M; Ajayan, P; Blase, X; Blau, W; Carroll, D; Charlier, J; Czerw, R; Foley, B; Grobert, N; Kamalakaran, R; Kohler-Redlich, P; Ruhle, M; et al. (2001)
The synthesis of crystalline C3N4 and CN nanotubes, predicted to be super-hard and metallic respectively, remains a challenge for the future. However, small quantities of nitrogen (< 15%) have been incorporated into carbon nanotubes and/or filaments. Particular attention will be focused on efficient self-assembly pyrolytic routes to large arrays (2.5 cm(2)) of aligned CNx nanotubes/nanofibers (15-80 nm od and < 100 microns length). These routes include hydrocarbon decomposition over preformed metal-cluster substrates and the pyrolysis organometallic compounds. State-of-the-art EELS that two N bonding types within the hexagonal C network occur. We note that it is difficult to generate highly ordered structures in which large concentrations of N are incorporated into the network [e.g. C9Nx (x less than or equal to 1)]. However, these 'hollow' fibers do not easily break upon bending and may behave as shock absorbing fillers in the fabrication of robust composites. The N-doped nanostructures have also been studied using tunneling spectroscopy. The electronic structure of these doped nanotubes has been strongly modified by including electron donor states near the conduction band edge. Finally, the role of boron in the creation of long carbon nanotubes (< 100 microns), using arc discharge techniques, exhibiting mainly zig-zag chirality will also be discussed in detail from an experimental and theoretical stand point. The results demonstrate that doping can greatly modify the electronic and mechanical properties of carbon nanotubes, thus paving the way to the creation of novel nanoscale devices.